Associations of muscle force, power, cross‐sectional muscle area and bone geometry in older UK men. Issue 4 (4th May 2017) - Zengin, Ayse; Pye, Stephen R.; Cook, Michael J.; Adams, Judith E.; Rawer, Rainer; Wu, Frederick C.W.; O'Neill, Terence W.; Ward, Kate A.
Abstract: Background: Ageing is associated with sarcopenia, osteoporosis, and increased fall risk, all of which contribute to increased fracture risk. Mechanically, bone strength adapts in response to forces created by muscle contractions. Adaptations can be through changes in bone size, geometry, and bending strength. Muscle mass is often used as a surrogate for muscle force; however, force can be increased without changes in muscle mass. Increased fall risk with ageing has been associated with a decline in muscle power—which is a measure of mobility. The aims of this study were as follows: (i) to investigate the relationship between muscle parameters in the upper and lower limbs with age in UK men and the influence of ethnicity on these relationships; (ii) to examine the relationships between jump force/grip strength/cross‐sectional muscle area (CSMA) with bone outcomes at the radius and tibia. Methods: White European, Black Afro‐Caribbean, and South Asian men aged 40–79 years were recruited from Manchester, UK. Cortical bone mineral content, cross‐sectional area, cortical area, cross‐sectional moment of inertia, and CSMA were measured at the diaphysis of the radius and tibia using peripheral quantitative computed tomography. Lower limb jump force and power were measured from a single two‐legged jump performed on a ground‐reaction force platform. Grip strength was measured using a dynamometer. Associations between muscle and bone outcomes was determined using linear regression with adjustments for age, height, weight, and ethnicity. Results: Three hundred and one men were recruited. Jump force was negatively associated with age; for every 10 year increase in age, there was a 4% reduction in jump force ( P < 0.0001). There was a significant age–ethnicity interaction for jump power ( P = 0.039); after adjustments, this was attenuated ( P = 0.088). For every 10 year increase in age, grip strength decreased by 11%. Jump force was positively associated with tibial bone outcomes: a 1 standard deviation greater jump force was associated with significantly higher cortical bone mineral content 3.1%, cross‐sectional area 4.2%, cortical area 3.4%, and cross‐sectional moment of inertia 6.8% (all P < 0.001). Cross‐sectional muscle area of the lower leg was not associated with tibial bone outcomes. Both grip strength and CSMA of the arm were positively associated, to a similar extent, with radius diaphyseal bone outcomes. Conclusions: Jump force and power are negatively associated with age in UK men. In the lower limb, the measurement of jump force is more strongly related to bone outcomes than CSMA. It is important to consider jump force and power when understanding the aetiology of bone loss and mobility in ageing men.